KKN Unimed 2025: dari Belimbing Tumbuh Ekonomi, dari Edukasi Lahir Generasi, dari Kebersamaan Hidup Harmoni Mahasiswa Kuliah Kerja Nyata Unimed 2025 Desa Durin Simbelang - Faridz Ravsamjani; Aanzar Mizana Nugraha; Aldira Lidwina Br Sembiring; Angelina Rolas Olivia Naibaно; Annisa Hidayah; Bella Amelia; Bonny Saragih; Daniel Sanggam Luhutan; Debby Ayu Andrera; Fifi Ivana Greace Sembiring; Firza Aditya Ramadhan; Fitri Novi Yanti Munthe; Josep Nainggolan; Juan Prima Saragih; Leysutha Kenina Grata Aka; Malvira Pohan; Noubel Putra Nainggolan; Selfiana Lumbanbatu; Sylvia Anasthasya Angel; Theodore Winn Tarigan; Tiara Sauna Br Sembiring; Vina Prd; Zahru Saritza (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
Community Service Program (KKN) is a form of student community service by directly applying scientific knowledge in the field. The 2025 Unimed KKN was conducted in Durin Simbelang Village, Pancur Batu District, Deli Serdang Regency, with the aim of empowering local potential and improving the quality of education, social, and environmental aspects of the village. This research used a qualitative descriptive approach with participatory methods, in which students actively engaged with the community in each program. Data were collected through observation, interviews, documentation, and direct participation, then analyzed descriptively through the stages of reduction, presentation, and conclusion. Research findings indicate that the Community Service Program (KKN) has had a significant impact in various aspects. In the economic sector, the downstreaming and marketing of processed starfruit products has successfully improved residents' skills in processing harvested produce into value-added products. In the educational sector, activities such as